Nordic cancer registration, a review of an invaluable source and example for surveillance, research and public health for more than 70 years - Storm Hans H. (Norsk Forening for Epidemiologi, 2022)
Cancer registration has been with us for decades surveilling societies for cancer incidence, trends, mortality and survival. Data are used for health care planning but even more so for research in cancer treatment, outcome and prevention - i.e. overall cancer control. With the 70th anniversary of the Cancer Registry of Norway, this paper examines the impact and role of the registry in the past and today for cancer registration and affiliated research in the Nordic countries, as well as scientific peer reviewed productivity. The Nordic collaboration in cancer-registry-based research benefits from previous and actual ongoing activities in Norway. The Cancer Registry of Norway is a prominent independent organization under Oslo University Hospital Trust for registration and registry-based cancer epidemiology, with a multidisciplinary broad-based high quality professional staff. The research portfolio includes regular cancer registration, linkage to external data e.g. occupation, biobanks and clinical data conducting analysis with clear national, Nordic and international relevance. Various threats to the ownership of cancer registries and the derived epidemiology in past, such as organizational changes and loss of independence were avoided in Norway, but the interpretation of data protection following the GDPR today causes delays or may even block the Nordic cancer registry research.